Rendahnya Minat Baca Peserta Didik Dalam Pembelajaran di SD GMIM IV Tomohon - Intan Nikita Pongoh (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this is to describe: Creating an interesting and fun school and literacy class environment with a reading corner so that children are interested and familiar with the literacy environment. Creating creative, innovative, flexible, easy and simple media with learning media to provide innovative reading activities that are fun, entertaining, not boring and creative. This type of research is a type of qualitative research with a descriptive approach. The descriptive approach is intended to describe the findings obtained after the research. The qualitative method is intended to obtain an in-depth understanding and interpretation of the meaning of phenomena in the field. The place where this research was carried out was SD GMIM IV Tomohon, which is located on Jalan Raya Tomohon-Manado, East Tomohon District, Tomohon City, North Sulawesi Province. Students are able to understand the importance of reading habits and their application in the learning process at school. As many students feel happy and happy when reading books. Students also really like learning that uses videos in which they describe something related to the material being taught. The researcher can conclude that: The understanding of students at SD GMIM IV Tomohon about the importance of reading habits is already in the high category. GMIM IV Tomohon Elementary teachers' understanding and ability in classroom management in relation to fostering students' interest in reading has improved along with the school's literacy program.